A3 receptor agonist modulates IL-1β hippocampus levels in a rat model of neuropathic pain - Cioato, Stefania Giotti; Fernandes Medeiros, Liciane; Costa Lopes, Bettega; Richardt Medeiros, Helouise; Caumo, Wolnei; Roesler, Rafael; Torres, Iraci LS (Clinical and Biomedical Research, 2022)
Introduction: Considering the lack of specific treatments for neuropathic pain, this study aimed to evaluate the effect of a single dose of adenosine A3 receptor IB-MECA on inflammatory and neurotrophic parameters in rats subjected to a neuropathic pain model. Methods: 64 adult male Wistar rats were used. Neuropathic pain was induced by chronic constriction injury (CCI) of the sciatic nerve and the treatment consisted of a 0.5 μmol/kg dose of IB-MECA, a selective A3 adenosine receptor agonist, dissolved in 3% DMSO; vehicle groups received DMSO 3% in saline solution, and morphine groups received 5 mg/kg. Cerebral cortex and hippocampus IL-1β, BDNF, and NGF levels were determined by Enzyme-Linked Immunosorbent assay. Results: The main outcome was that a single dose of IB-MECA was able to modulate the IL-1β hippocampal levels in neuropathic pain induced by CCI and the DMSO increased IL-1β and NGF hippocampal levels in sham-operated rats. However, we did not observe this effect when the DMSO was used as vehicle for IB-MECA, indicating that IB-MECA was able to prevent the effect of DMSO. Conclusions: Considering that the IL-1β role in neuropathic pain and the contributions of the hippocampus are well explored, our result corroborates the relationship between the A3 receptor and the process of chronic pain maintenance.